CLIMATE CHANGE AND VARIABILITY FARM-LEVEL ADAPTATION STRATEGY FOR SUSTAINABLE SOYBEAN PRODUCTION IN RAINFOREST AGRO-ECOLOGY, NIGERIA - Adetayo, A.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Field experiments were conducted during the 2021 and 2022 planting seasons at the Laboratory for Geo-ecology and sustainable food systems, Federal University of Technology Akure and Institute of Agricultural Research and Training Ibadan. Both locations are within the rain-forest agro-ecological zone of Nigeria. The varieties of soybean used are, IT1498 (V1), IT1951 (V2) and TGX1448-2E (V3). The three planting dates selected for are 28th April, 12th of May and 26th of May in 2021 and 16th April, 30th of April and 14th of May in 2022. Cultivar differences were noticed among the three varieties soybean which indicated their generic differences. Generally, the growth and yield parameters of soybean decreased with delayed planting irrespective of the variety, locations and year of planting. The average yield of soybean reduced with delayed planting as 1821.34 kgha-1, 1663.67 kgha-1 and 1504.0 kgha-1 from planting dates 1 to 3 respectively. Yields of Soybean planted in Ibadan was more (1671.99 kgha-1) than those in Akure (1654.16 kgha-1). Planting season on the other hand, 2021 produced more yield of soybean (1665 kgha-1) than 2022 (660 kgha-1). Among the soybean varieties, IT1498 had the highest yield (1716.31 kgha-1), followed by IT1951 (1649.55 kgha-1) and TGX1448-2E (1623.38 kgha-1). Farmers are advised to Plant soybean at the onset of rains for optimum yield of the crop.